UPAYA PELESTARIAN BAHASA LAMPUNG TENTANG PENGGUNAAN BAHASA LAMPUNG DI KALANGAN SEKOLAH MENENGAH - Rani Oktavia; Fifi Mutia Sari; Mulyanto Widodo; Rahmat Prayogi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Regional languages ​​reflect the cultural values ​​and identity of a society, and also shape the character of the nation. Due to globalization, urbanization, and socio-cultural changes, Lampung, one of the regional languages ​​in Indonesia, is now facing many challenges. The purpose of this study is to explain the use of Lampung in secondary schools and to identify factors influencing its decline, as well as efforts to preserve it through formal education. This study used a qualitative approach and library research methods. Data were collected from various written sources, including books, scientific journals, and official documents related to the topic of regional language preservation. As this study demonstrates, preserving Lampung through formal education is a strategic step to strengthen regional cultural identity and shape the character of the younger generation, whose local values ​​are being eroded by the influence of globalization.